2007
DOI: 10.1056/nejmoa066254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bariatric Surgery on Mortality in Swedish Obese Subjects

Abstract: Bariatric surgery for severe obesity is associated with long-term weight loss and decreased overall mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

84
2,433
6
230

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 4,149 publications
(2,753 citation statements)
references
References 34 publications
84
2,433
6
230
Order By: Relevance
“…Surgical approaches should be reserved for morbid obese patients (BMIX40 kg m -2 ) with hypertension and other major comorbidities. 80 In the prospective, controlled Swedish Obese Subjects study, 82 subjects who underwent bariatric surgery had lower overall mortality and long-term weight loss, during an average of 10.9 years of follow-up, compared with a matched control group that received conventional treatment. The surgery group had lower 10-year incidence rates of diabetes, hypertriglyceridemia and hyperuricemia, but not of hypertension than the control group.…”
Section: Endothelial Dysfunction and Changes In Vascular Structurementioning
confidence: 99%
“…Surgical approaches should be reserved for morbid obese patients (BMIX40 kg m -2 ) with hypertension and other major comorbidities. 80 In the prospective, controlled Swedish Obese Subjects study, 82 subjects who underwent bariatric surgery had lower overall mortality and long-term weight loss, during an average of 10.9 years of follow-up, compared with a matched control group that received conventional treatment. The surgery group had lower 10-year incidence rates of diabetes, hypertriglyceridemia and hyperuricemia, but not of hypertension than the control group.…”
Section: Endothelial Dysfunction and Changes In Vascular Structurementioning
confidence: 99%
“…in 1995 82. Strong evidence has shown that bariatric surgery is an effective treatment for severe obesity (BMI >35 kg/m 2 ) and results in marked improvement of T2DM control 10, 83, 84. Derived from bariatric surgery, metabolic surgery is focused on T2DM treatment in mildly obese or overweight patients (BMI <35 kg/m 2 ) 85.…”
Section: From Bariatric To Metabolic Surgerymentioning
confidence: 99%
“…Unfortunately, current medical treatment has been relatively unsatisfactory in the treatment of obesity as well as T2DM 7, 8. Bariatric surgery, a weight reduction surgery, has been shown as not only an effective treatment for severe obesity (BMI >35 kg/m 2 ) but has also resulted in marked improvement of T2D control 9, 10. Encouraged by the success of bariatric surgery, gastrointestinal metabolic surgery has been recently proposed as a new treatment modality for obesity‐related T2DM in patients with BMI <35 kg/m 2.…”
Section: Introductionmentioning
confidence: 99%
“…Current anti-obesity drugs are moderately effective at achieving weight loss, but considerable adverse effects can occur. Presently, the only effective treatment with a proven mortality benefit is bariatric surgery (7,8) . The mechanisms underlying the effectiveness of these surgical techniques are not completely understood but alterations in circulating gut hormone levels have been shown to be an important factor (9)(10)(11) .…”
Section: Bariatric Surgery: Appetite Control Model: Gut Hormones: Obementioning
confidence: 99%